(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
The article seeks to inquire about the link between Wittgenstein’s elaborations and psychoanalysis. Reasoning stops at Wittgenstein’s proposals on the self-referential impossibility of language, ethical acts and psychoanalysis. In this context, he sketches a possible response to the criticisms that Wittgenstein directed to psychoanalysis, pondering them from three central notions in Jacques Lacan’s work: causality, fiction and the idea of subject. In a second time, the article proposes to think about the link between ethics and subjectivity, from the temporality which introduces, in the human perspective, the dynamic drive.